Magnetic and Highly Luminescent Heterostructures of Gd3+/ZnO Conjugated to GCIS/ZnS Quantum Dots for Multimodal Imaging - Bruna Lallo da Silva; Laurent Lemaire; Jean-Pierre Benoit; Fernanda Hediger Borges; Rogéria Rocha Gonçalves; Camila Fernanda Amantino; Fernando Lucas Primo; Leila Aparecida Chiavacci (Nanomaterials, 2021)
In recent years, the use of quantum dots (Qdots) to obtain biological images has attracted attention due to their excellent luminescent properties and the possibility of their association with contrast agents for magnetic resonance imaging (MRI). In this study, Gd3+/ZnO (ZnOGd) were conjugated with Qdots composed of a gadolinium-copper-indium-sulphur core covered with a ZnS shell (GCIS/ZnS Qdots). This conjugation is an innovation that has not yet been described in the literature, and which aims to improve Qdot photoluminescent properties. Structural and morphological Qdots features were obtained by transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and thermogravimetric analyses (TGA). The photoluminescent properties were examined by emission (PL) and excitation (PLE) spectra. A new ZnOGd and GCIS/ZnS (ZnOGd-GCIS/ZnS) nanomaterial was synthesized with tunable optical properties depending on the ratio between the two native Qdots. A hydrophilic or lipophilic coating, using 3-glycidyloxypropyltrimethoxysilane (GPTMS) or hexadecyltrimethoxysilane (HTMS) on the surface of ZnOGd-GCIS/ZnS Qdots, was carried out before assessing their efficiency as magnetic resonance contrast agents. ZnOGd-GCIS/ZnS had excellent luminescence and MRI properties. The new Qdots developed ZnOGd-GCIS/ZnS, mostly constituted of ZnOGd (75%), which had less cytotoxicity when compared to ZnOGd, as well as greater cellular uptake.